Implementasi Desain Kolam Pemandian Anak Menggunakan Green Concreate Sebagai Spot Wisata Embung Desa Banjarejo - Ansyorie, M. Musthofa; Ariestadi, Dian; Leksono, Duwi; I, M. Aris; Setia Budi, Kevin Reznadya (Jurnal Inovasi Teknologi dan Edukasi Teknik, 2023)
The development of the Embung Area of Banjarejo Village into an education- and nature-based tourism area continues to this day. In the initial design of the bung area of Banjarejo village, in addition to the concept of water-based educational tourism, a tourist area is currently developed to attract interest from children. One of the area's developments is the development of bathing pool spots for children. This children's bathing pool will be side by side with several spots such as playgrounds, photo spots, etc. Other problems that arise related to the realization plan of the children's bathing pool spot are related to technicalities such as the details of the pool building, assistance in the implementation of pool work, and product quality, which is expected to get satisfactory results and of course be part of improving the economy of residents or village income. The existence of this pool will later become a tourist area managed by Bumdes. Based on the above problems, solutions to solve these problems include (a) Making a children's bathing pool design by applying the concept of green concrete, (b) Implementation of the design of a children's bathing pool at the location of the Banajrejo village embung tourist area. Pengembangan Kawasan Embung Desa Banjarejo menjadi suatu kawasan wisata berbasis edukasi dan alam hingga saat ini terus berlangsung. Pada rancangan awal dikawasan embung desa banjarejo ini selain dikonsep wisata edukasi berbasis air, saat ini dikembangkan pula area wisata untuk menarik minat dari kalangan anak-anak. Salah satu pengembangan area tersebut adalah pengembangan spot kolam pemandian untuk anak-anak. Kolam pemandian anak ini rencananya berdampingan dengan beberapa spot seperti playground, spot foto, dan lain sebagainya. Permasalahan lain yang muncul terkait rencana realisasi spot kolam pemandian anak adalah terkait dengan teknis seperti detail bangunan kolam, pendampingan pelaksanaan pekerjaan kolam, dan mutu produk yang diharapkan mendapatkan hasil yang memuaskan dan tentunya menjadi bagian dari peningkatan ekonomi warga ataupun pendapatan Desa. Keberadaan kolam ini nantiya akan menjadi area wisata yang dikelola oleh Bumdes. Berdasarkan pada permasalahan di atas, solusi untuk menyelesaikan masalah tersebut diantaranya adalah (a) Pembuatan desain kolam pemandian anak dengan menerapkan konsep green concrete, (b) Implementasi desain Kolam Pemandian anak dilokasi kawasan wisata embung desa Banjarejo.